Current status of brachytherapy in Korea: a national survey of radiation oncologists - Kim, Haeyoung (J Gynecol Oncol, 2016)
OBJECTIVE: The aim of the present study was to acquire information on brachytherapy resources in Korea through a national survey of radiation oncologists. METHODS: Between October 2014 and January 2015, a questionnaire on the current status of brachytherapy was distributed to all 86 radiation oncology departments in Korea. The questionnaire was divided into sections querying general information on human resources, brachytherapy equipment, and suggestions for future directions of brachytherapy policy in Korea. RESULTS: The response rate of the survey was 88.3%. The average number of radiation oncologists per center was 2.3. At the time of survey, 28 centers (36.8%) provided brachytherapy to patients. Among the 28 brachytherapy centers, 15 (53.5%) were located in in the capital Seoul and its surrounding metropolitan areas. All brachytherapy centers had a high-dose rate system using (192)Ir (26 centers) or (60)Co (two centers). Among the 26 centers using (192)Ir sources, 11 treated fewer than 40 patients per year. In the two centers using (60)Co sources, the number of patients per year was 16 and 120, respectively. The most frequently cited difficulties in performing brachytherapy were cost related. A total of 21 centers had a plan to sustain the current brachytherapy system, and four centers noted plans to upgrade their brachytherapy system. Two centers stated that they were considering discontinuation of brachytherapy due to cost burdens of radioisotope source replacement. CONCLUSION: The present study illustrated the current status of brachytherapy in Korea. Financial difficulties were the major barriers to the practice of brachytherapy.